Diffusible signal factor primes plant immunity against Xanthomonas campestris pv. campestris (Xcc) via JA signaling in Arabidopsis and Brassica oleracea - Zhao, Qian; Liu, Fang; Song, Cong; Zhai, Tingting; He, Ziwei; Ma, Limei; Zhao, Xuemeng; Jia, Zhenhua; Song, Shuishan (Frontiers in Cellular and Infection Microbiology, 2023)
Many Gram-negative bacteria use quorum sensing (QS) signal molecules to monitor their local population density and to coordinate their collective behaviors. The diffusible signal factor (DSF) family represents an intriguing type of QS signal to mediate intraspecies and interspecies communication. Recently, accumulating evidence demonstrates the role of DSF in mediating inter-kingdom communication between DSF-producing bacteria and plants. However, the regulatory mechanism of DSF during the Xanthomonas-plant interactions remain unclear. In this study, we found that the low concentration of DSF could prime plant immunity against Xanthomonas campestris pv. campestris (Xcc) in both Brassica oleracea and Arabidopsis thaliana. Pretreatment with DSF and subsequent pathogen invasion triggered an augmented burst of ROS by DCFH-DA and DAB staining. CAT application could attenuate the level of ROS induced by DSF. The expression of RBOHD and RBOHF were up-regulated and the activities of antioxidases POD increased after DSF treatment followed by Xcc inoculation. Transcriptome combined with metabolome analysis showed that plant hormone jasmonic acid (JA) signaling involved in DSF-primed resistance to Xcc in Arabidopsis. The expression of JA synthesis genes (AOC2, AOS, LOX2, OPR3 and JAR1), transportor gene (JAT1), regulator genes (JAZ1 and MYC2) and responsive genes (VSP2, PDF1.2 and Thi2.1) were up-regulated significantly by DSF upon Xcc challenge. The primed effects were not observed in JA relevant mutant coi1-1 and jar1-1. These results indicated that DSF-primed resistance against Xcc was dependent on the JA pathway. Our findings advanced the understanding of QS signal-mediated communication and provide a new strategy for the control of black rot in Brassica oleracea.